Ring opening and skeletal reconstruction of 3-vinyl benzofuranone-chromone synthons: catalyst-free access to skeletally-diverse 2-pyridone and optically active imidazoline derivatives. Issue 11 (3rd March 2022) - Wang, Wei-Na; Liu, Ren-Ming; Zhang, Lei; Liu, Xiong-Li; Dai, Yi-Feng; Yu, Zhang-Biao; Peng, Li-Jun
Abstract : Herein is reported the first example of ring opening and skeletal reconstruction of 3-vinyl benzofuranone-chromones 1 as versatile synthons for the synthesis of functionalized 2-pyridones 3 in good to excellent yields. Abstract : Herein is reported the first example of ring opening and skeletal reconstruction of 3-vinyl benzofuranone-chromones 1 as versatile synthons, which can react with ammonia or primary aliphatic amines as binucleophiles, for the eco-friendly and atom-economical synthesis of diverse and functionalized 2-pyridones 3 with potential biological activity in good to excellent yields (77–93%). When using optically active 1, 2-diphenylethylenediamine 2 as the binucleophile, the in situ generated 2-pyridone intermediates are successfully transformed to novel optically active functionalized imidazoline derivatives 4 with high efficiency (up to 87% yield). In particular, this is the first report on the catalyst-free intramolecular cyclization occurring between an amide and a primary aliphatic amine for the construction of imidazoline molecules.